Novel high entropy alloys as binder in cermets: From design to sintering. (September 2021) - Prieto, E.; Vaz-Romero, A.; Gonzalez-Julian, J.; Guo, S.; Alvaredo, P.
Abstract: In recent years a new group of alloys has emerged breaking with the classical alloying concepts of physical metallurgy, high entropy alloys (HEA). Their main characteristic is that these alloys present 4 or 5 main elements increasing the entropy of the system and favouring the formation of a single phase. The disordered solid solution leads to develop an alloy with improved properties, in particular high thermal stability, hardness and strength. These properties make this group of alloys attractive as potential candidates for alternative binders in hard materials. In this work, two new compositions have been designed with the aim of obtaining a single BCC phase, reducing the cost and minimizing the presence of critical elements using elements that can present good potential properties for a cermet and with low toxicity and price such as Al, Cr, Mo, Ni, Fe and Ti. The design has been made based on the composition calculation applying the HEA phase formation empirical rules from literature in combination with thermodynamic simulations by Calphad method. The viability of the compositions has been studied through the processing of the compositions by casting and the study of wettability and solubility at high temperature on the hard phase of TiCN. Once the chosen compositions have been validated as competitive binders, cermets have been consolidated by spark plasma sintering (SPS) and the influence of the compositions on the mechanical properties of the compound materials has been studied. Graphical abstract: Unlabelled Image Highlights: Design of new HEAs intended as alternative binders. Study of wetting between HEA binders and TiCN hard phase. Influence of HEA composition on mechanical properties of the cermets. New alloy as binder avoiding critical elements.